2015
DOI: 10.1111/jnc.13353
|View full text |Cite
|
Sign up to set email alerts
|

Sipa1l3/SPAR3 is targeted to postsynaptic specializations and interacts with the Fezzin ProSAPiP1/Lzts3

Abstract: Rap GTPase-activating proteins (RapGAPs) are essential for synaptic function as they tightly regulate synaptic Rap signaling. Among the most abundant synaptic RapGAPs in brain are the Spine-associated RapGAPs (SPARs) Sipa1l1/ SPAR and Sipa1l2/SPAR2, whereas nothing has been reported on Sipa1l3/SPAR3. In this study, we show that Sipa1l3/SPAR3 is conserved across species, has a distinct expression pattern in the developing rat brain and is localized at excitatory postsynapses. We further demonstrate that the Sip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…In a previous study, we confirmed the genomic conservation of the sipa1l3 gene across species (Dolnik et al, 2016). Here, we showed a similar expression and function of Sipa1l3 in Xenopus compared with mouse and zebrafish (Greenlees et al, 2015;Lachke et al, 2012;Rothe et al, 2016).…”
Section: Sipa1l3 Is Required For Ocular Developmentsupporting
confidence: 66%
See 3 more Smart Citations
“…In a previous study, we confirmed the genomic conservation of the sipa1l3 gene across species (Dolnik et al, 2016). Here, we showed a similar expression and function of Sipa1l3 in Xenopus compared with mouse and zebrafish (Greenlees et al, 2015;Lachke et al, 2012;Rothe et al, 2016).…”
Section: Sipa1l3 Is Required For Ocular Developmentsupporting
confidence: 66%
“…As Epha4 is located at the cell membrane and Sipa1l3 is located in the cytoplasm close to the cell membrane (Dolnik et al, 2016), we hypothesized Epha4 to be functionally upstream of Sipa1l3. We performed rescue experiments by injecting the Epha4 MO together with rat sipa1l3 RNA and observed a significant reduction in the number of embryos exhibiting eye abnormalities including the microphthalmia phenotype ( Fig.…”
Section: Epha4 Is Upstream Of Sipa1l3 During Xenopus Eye Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we report our efforts to identify genetic modifiers in CMT1A on a genome‐wide scale using a large cohort of 971 CMT1A patients. We identified 4 strongly associated intronic variants in signal‐induced proliferation‐associated 1 like 2 ( SIPA1L2 ), also known as spine‐associated RapGAP2 ( SPAR2 ), a member of the Rap GTPase‐activating proteins (RapGAPs) enriched at synaptic sites . Our functional studies imply a role in peripheral nerve myelination and regulating PMP22 expression.…”
mentioning
confidence: 84%